The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1063/1.362746
|View full text |Cite
|
Sign up to set email alerts
|

Reabsorption, band-gap narrowing, and the reconciliation of photoluminescence spectra with electrical measurements for epitaxial n-InP

Abstract: The effects of reabsorption and band-gap narrowing (BGN) on experimental photoluminescence (PL) spectra of n-InP grown by metalorganic chemical vapor deposition are analyzed. PL spectra show a pronounced widening of the main PL peak and a shift of that peak to higher photon energy with increasing doping due to band filling. However, the magnitude of these effects, both here and in earlier studies of n-type III–V semiconductors, is smaller than expected based upon band filling calculations and electrical measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
5
33
0
2
Order By: Relevance
“…The discrepancy of BGN between the experimental result and the Jain theory is clearly seen at high doping level. Very similar discrepancies have been observed for n-InP [48]. Sieg and Ringel [48] have given three possible explanations in the case of n-GaAs and n-InP between the theoretical BGN calculated from Eq.…”
Section: Band Gap Shrinkage Due To Doping Effectmentioning
confidence: 59%
See 2 more Smart Citations
“…The discrepancy of BGN between the experimental result and the Jain theory is clearly seen at high doping level. Very similar discrepancies have been observed for n-InP [48]. Sieg and Ringel [48] have given three possible explanations in the case of n-GaAs and n-InP between the theoretical BGN calculated from Eq.…”
Section: Band Gap Shrinkage Due To Doping Effectmentioning
confidence: 59%
“…Very similar discrepancies have been observed for n-InP [48]. Sieg and Ringel [48] have given three possible explanations in the case of n-GaAs and n-InP between the theoretical BGN calculated from Eq. (10) and experimental BGN obtained by PL.…”
Section: Band Gap Shrinkage Due To Doping Effectmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, Fu et al [16] provide a convenient 1 m formula to determine free-electron concentration in InN films by PL measurement. The relationship between FWHM and freeelectron concentration can be well described by the empirical formula [17,18]. The free electron concentration was estimated as $7 Â 10 18 and $2 Â 10 19 cm À 3 , respectively, for the CM and PM growth of InN nanodots.…”
Section: Resultsmentioning
confidence: 99%
“…Both thermionic and tunneling currents are exponentially related to built in potential. It is found that the BGN in n-InP is higher than that of n-GaAs [120]. The BGN in AlAs and GaP are higher than that of InP, GaAs and InAs due to higher conduction band density of states and lower relative permittivity of these materials [112,121].…”
Section: Doping Issues In Iii-v Semiconductorsmentioning
confidence: 99%